The Impact of Civil-Military Relations on Institutional Discrimination against the Rohingya during the Government of the NLD Party - Shaffira Aliffa Maharani (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2025)
This article aims to describe the reasons behind institutional discrimination towards the Rohingya in Myanmar during the National League for Democracy (NLD) government headed by Aung San Suu Kyi in 2016-2021. The 2015 general election victory of the NLD sparked great optimism for reforms across several sectors in Myanmar, particularly regarding the improvement of conditions for the Rohingya ethnic minority. By using qualitative method, this article examines the relationship between the government of the NLD Party and the military 'Tatmadaw' by assessing four cultural and institutional indicators using concordance theory by Schiff (2008). Inequality in civil-military relations is demonstrated by the lack of agreement (discordance) in military style, recruitment methods, the role and social composition of the armed forces, and political decision-making processes. This disparity played a pivotal role in the Rohingya ethnic cleansing operations in 2016 and 2017, and in the ongoing discrimination against the Rohingya as a whole. Over the years, discrimination against the Rohingya has been fueled by propaganda supported by influential monks, which succeeded in creating anti-Rohingya sentiment among the population. This factor is a form of institutional discrimination that significantly fueled animosity towards the Rohingya throughout the NLD Party government's tenure.The longstanding systematic discrimination against the Rohingya has facilitated the Tatmadaw's military operations in Rakhine.